(untitled) (Journal of the College of Basic Education, 2026)
This study aims to Identify self-advocacy among kindergarten teachers as well as the differences in the significance of emotional confidence among kindergarten teachers according to the service variable. To achieve these goals, the researcher followed the descriptive approach. The study population consisted of kindergarten teachers in Wasit Governorate. The study sample was selected from 400 teachers using the stratified random sampling method with proportional dIstribution. To measure self-advocacy, the researcher developed a scale based on Harris’s (2009) model. The scale consists of 31 Items distributed over five dimensions. The psychometric properties of the scale were verified through the discriminatory power and the correlation coefficient between the items and the total score. The validity and reliability of the scale were also confirmed, with the test-retest reliability coefficient reaching 0.821, while the Cronbach’s alpha coefficient reached 0.813. Research results: Kindergarten teachers enjoy a high level of self-advocacy. It was found that there Is a difference in advocacy according to the length of service, and this difference favors teachers who have had more than (15) years of service. It has been shown here that long experiencee is a supporting factor for self-advocacy.